Size controlled synthesis of core-shell gold nanoparticles for photothermal application - Chung, Siok Koon (2016)
The purpose of this report is to investigate and understand a newly developed strategy, in which mussel-inspired polydomaine (PDA) has been used to construct core-shell plasmonic gold nanoparticles. With the use of PDA, the core is now no longer restricted to just spherical metal cores, but all types of components due to the unique adhesive and redox properties of robust PDA. The distance between the core and shell of the nanoparticles can be tailored easily from 5 to 13 nm, by adding different concentration of dopamine in, so as to adjust the region of spectrum from visible to near-infrared of these nanoparticles. This experiment has made use of the following characterization techniques, which included the Transmission Electron Microscopy (TEM) and UV-vis Spectrometer to observe shapes and sizes of the nanoparticles, their optical properties such as localized surface plasmon resonance (LSPR) and photothermal conversion. Hence, with this newly developed strategy, it brings about a great potential to a variety of application such as sensing, nanophotonics, nanomedicine and many more.